Deteksi Wajah dalam Foto Menggunakan Teknologi Visi Komputer - Supiyandi Supiyandi; Tegar Ardiansyah; Sri Putri Balqis; Jundi Haqqoni; Salsa Nabila Iskandar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study discusses the implementation of computer vision technology for face detection in photos using two sample images with variations in lighting and face pose. The developed system combines the Viola-Jones algorithm and Convolutional Neural Networks (CNN) to enhance resilience against lighting and face orientation variations. Experimental results show high accuracy even with only two sample images. This research also develops preprocessing techniques to handle extreme lighting conditions and demonstrates efficient implementation using Python and OpenCV.